Ultrasonography and Magnetic Resonance Cholangiopancreatography in Patients with Obstructive Jaundice - Chhettri, Pramod; Rana, Hari (Journal of College of Medical Sciences-Nepal, 2020)
Background: Jaundice is a common presenting symptom in patients with hepatobiliary disease. It can be categorized into medical and surgical jaundice and it is important to differentiate due to the different treatment options Methods: In this cross sectional study from Jan 2017 to June 2018, 84 consecutive patients with obstructive jaundice who underwent initial USG and then MRCP were included and their respective diagnosis compared keeping surgery and/or histopathology as the gold standard for final diagnosis. Results: Out of 84 patients, 67.9% were females and 32.1% were males. The most common cause for obstructive jaundice was benign in 72.6% and malignancy in 27.4%. Among the benign lesions choledocholithiasis was the most common (57.4%) followed by pancreatitis (26.2%). Cholangiocarcinoma was the most common malignant cause (47.8 %) followed by periampullary carcinoma (26.2%). The sensitivity and specificity of USG in benign lesions was 67.2% and 87% respectively, and in malignancy 56% and 95% respectively. Similarly sensitivity and specificity of MRCP for benign lesions was 95.2% and 90.9% respectively, and for malignancy 95.75% and 98.45%respectively. Overall diagnostic accuracy of USG in benign and malignant causes was 76.62% and 84.52% respectively. Similarly overall diagnostic accuracy of MRCP for benign and malignant causes was 93.98% and 97.6% respectively. Conclusions: USG is a good modality for Initial screening and for differentiating medical and surgical cause of jaundice. MRCP is a better modality with higher sensitivity, specificity and diagnostic accuracy for detecting pathology as compared to USG. Keywords: MRCP; obstructive jaundice; USG.